Comparative study of Chemical Pathology sample collection tubes at the largest hospital in South Africa: Comparison between BarricorTM and serum separator tubes - Khoza, Siyabonga; Ford , Sarah; Buthelezi, Ernest; Tanyanyiwa, Donald (Journal of Medical Biochemistry, 2021)
Background: BarricorTM lithium heparin plasma tubes are new blood tubes that have been introduced to overcome the effects of gel in serum separator tubes (SST) and the shortcomings of standard lithium heparin plasma. We aimed to evaluate BarricorTM tubes as an alternative to serum separator tubes and compare the stability between the tubes.Methods: Forty-four paired samples were collected using both BarricorTM and SST. We compared five analytes at baseline (
Keywords: Blood collection devises; BarricorTM; Serum separator tubes